Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Pendekatan Scientific di Sekolah Dasar - Vina Iasha (Institut Agama Islam Negeri (IAIN) Curup, 2018)
: This study aims to describing the improvement of thematic learning process by using scientific approach in Grade 1 Elementary School of 04 Birugo Bukittinggi. This research used qualitative and quantitative approach. This research was classroom action research and had two cycles. The research subject was a teacher and 30 students of Grade 1 Elementary School of 04 Birugo Bukittinggi. The study’s results shows the increasing in: Lesson plan of the first cycle is meeting 1 77,77% (good), meeting 2 88,89% (good), and the second cycle meeting 1 is 94,44% (very good), meeting 2 97,22% (very good). Teacher’s activities in first cycle meeting 1 is 78,33% (good), meeting 2 86,67% (good), the second cycle meeting 1 is 93,33% (very good), meeting 2 96,67% (very good). Student’s activities in first cycle meeting 1 is 78,33% (good), meeting 2 86,67% (good), the second cycle meeting 1 is 93,33% (very good), meeting 2 96,67% (very good). Therefore, the scientifict method can increase the integrated thematic learning at elementary school